Durability performance of lightweight concrete containing palm oil fuel ash as mixing ingredient - Yamuneshwary, R. Subramaniam (2019)
Malaysia as the world‘s largest exporter of palm oil has been facing problem in disposing palm oil fuel ash, a by- product of palm oil mill since years ago. The abundant production of waste material from palm oil plantation which disposed at landfill will cause environmental degradation and it is harmful to the ecosystem or ecological imbalance if there is no proper action taken to reduce it. This research investigates the durability of lightweight concrete containing various percentage of POFA replacement when subjected to acidic and sulphate environment. All the specimens were subjected to water curing for 28 days before immersed in the hydrochloric solution having pH 2 for 1800 hours. The specimens also being subjected to sodium sulphate solution for 16 weeks. The strength deterioration was evaluated through mass changing of the specimens and compressive strength determinations. The finding shows that 20% of POFA replacement enhances the resistance of lightweight concrete towards acid attack and sulphate attack.